(untitled) (Palíndromo, 2019)
The work of José Leonilson is one of the most emblematic productions of contemporary Brazilian art and the most significant for the reflection on the rela-tionship between verbal and visual lan-guages. His production is a remarkable case of insertion of words into plastic production. However, it is an insertion in which, in addition to possessing poetic status, words acquire meaning through their formal presentation and the spa-tial characteristic of drawings, paintings and embroidery. We believe that such production is significant to reflect on the methodologies of analysis proposed by the interarts field, since it is able to assess the effectiveness of such methodologies. In this sense, we propose an analysis of the methodology and nomenclature of analysis initially proposed by Leo Hoeck for the interart studies against the analy-sis of some works by Leonilson. The ini-tiative is justified in the face of the chal-lenge of thinking about the implications of using such methodologies for the translation of Leonilson’s work into En-glish, for example. We will base the analy-sis initially on a brief reflection on some bibliographical references that analyse the relationship between arts and litera-ture, as well as the analysis of Leonilson’s works, as well as his interest in poetry.